ENGARUH PENGGUNAAN LARUTAN KUMUR EKSTRAK BUAH NANAS (Ananas comosus L. Merr) TERHADAP PENURUNAN JUMLAH NEUTROFIL DALAM CAIRAN SULKUS GINGIVA PADA PENDERITA GINGIVITIS RINGAN - Raissa Febrina; Almurdi Almurdi; Kosno Suprianto (Faculty of Dentistry Universitas Andalas, 2013)
Gingivitis is defined as gingival inflammation caused by dental plaque accumulation. Bacteria in the plaque is releasing toxin that would trigger neutrophil to move to gingival sulcus as a main protection. Plaque control mechanically or chemically will be an effective prevention and care for gingivitis. Chemical control is done by mouthwash. Pineapple extract (Ananas comosus L.merr) contains bromelain which has antibacterial and antiinflammation features. The aim of this study was to find the effect of using pineapple-extracted mouthwash (Ananas comosus L. Merr) toward neutrophil count drop in gingival crevicular fluid of mild gingivitis patients. This study was quasy experimental using pre-test and post-test design, conducted to 21 patients having mild gingivitis with gingival crevicular fluid were taken by paperpoint 30 for 30 seconds. The neutrophil count was done with microscope. Paired T-test analysis showed that there was significant reduction of neutrophil count before and after the intervention (p<0.05). Mouthwash using 50 % pineapple-extracted solution for four days was proven to reduce neutrophil count in gingival crevicular fluid of mild gingivitis patients.